Inverted Basal Shear Stress of Antarctic and Greenland Ice Streams and Glaciers - Sergienko, Olga (IEDA: US Antarctic Program Data Center, 2015)
This data set includes basal shear distributions inferred from surface observations - surface ice velocities (Joughin et al., 2010, Rignot et al., 2011), bed and surface elevations (Fretwell et al., 2013) under ten selected locations in Greenland and Antarctica. In Greenland, the locations were: 79° North and Zachariae Glaciers, Jakobshan Isbrae, North East Greenland Ice Stream, Petermann Glacier. The Antarctica locations were Bindschadler Ice Stream, Lambert Ice Stream, MacAyeal Ice Stream, Pine Island Glacier, Thwaites Glacier, and an unnamed location around ~40° E 84° S.